Analysis of lightning electromagnetic field propagation in mountainous terrain and its effects on ToA‐based lightning location systems. Issue 2 (27th January 2016) - Li, Dongshuai; Azadifar, Mohammad; Rachidi, Farhad; Rubinstein, Marcos; Diendorfer, Gerhard; Sheshyekani, Keyhan; Zhang, Qilin; Wang, Zhenhui
Abstract: In this paper, we analyze the propagation effects on lightning‐radiated electromagnetic fields over mountainous terrain by using a three‐dimensional (3‐D) finite difference time domain (FDTD) method. We also discuss the time delay error in the time‐of‐arrival (ToA) technique currently used to locate lightning in detection networks, specifically. Furthermore, the accuracy of different approximate methods presented in the literature is discussed and tested by using our 3‐D FDTD method. It is found that (1) the time delays and amplitudes of the lightning‐radiated electromagnetic fields can be significantly affected by the presence of a mountainous terrain and associated diffraction phenomena; (2) for a finitely conducting ground, the time delay shows a slight increase with the increase of the observation distance, but the time delay resulting from the finite ground conductivity appears to be smaller than that caused by the mountainous terrain; and (3) the timing error associated with the ToA technique depends on the threshold times. Threshold times of 10% and 20% of the peak provide very similar results compared to those corresponding to the peak of the first derivative of the magnetic field, and the threshold time exceeds 50% of the initial rising amplitude of the signal. Furthermore, we have assessed the accuracy of two simplified methods (terrain‐envelope method and tight‐terrain fit method) to account for the time delays resulting from the propagation in a mountainous terrain. It is found that both methods result in time delays that are in reasonable agreement but always overestimating the results obtained using the full‐wave 3‐D FDTD approach for the perfectly conducting ground. These two methods represent interesting alternatives to account for the time delay over a nonflat terrain using the terrain model. Key Points: Lightning fields can be significantly affected by the presence of mountainous terrain ToA timing errors due to propagation along mountainous terrain depend on the threshold times Two simplified methods are shown to reproduce the propagation time delays in mountainous terrain